2012
DOI: 10.1158/1078-0432.ccr-11-2703
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I First-in-Human Trial of Bardoxolone Methyl in Patients with Advanced Solid Tumors and Lymphomas

Abstract: Purpose Bardoxolone methyl, a novel synthetic triterpenoid and antioxidant inflammation modulator, potently induces Nrf2 and inhibits NF-κB and Janus-activated kinase/STAT signaling. This first-in-human phase I clinical trial aimed to determine the dose-limiting toxicities (DLT), maximum tolerated dose (MTD), and appropriate dose for phase II studies; characterize pharmacokinetic and pharmacodynamic parameters; and assess antitumor activity. Experimental Design Bardoxolone methyl was administered orally once… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
172
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(175 citation statements)
references
References 37 publications
3
172
0
Order By: Relevance
“…Daily oral administration of fumaric acid esters over 12 weeks was associated with the increased expression of NRF2 target genes in the skin of patients with psoriasis (Onderdijk et al, 2014). Similarly, a fivefold increase in the mRNA level of NQO1 has been reported in peripheral blood mononuclear cells obtained from cancer patients that received a daily dose of CDDO-Me for 3 weeks (Hong et al, 2012).…”
Section: Biomarkers As Nuclear Factor (Erythroidderived 2)-like 2mentioning
confidence: 87%
“…Daily oral administration of fumaric acid esters over 12 weeks was associated with the increased expression of NRF2 target genes in the skin of patients with psoriasis (Onderdijk et al, 2014). Similarly, a fivefold increase in the mRNA level of NQO1 has been reported in peripheral blood mononuclear cells obtained from cancer patients that received a daily dose of CDDO-Me for 3 weeks (Hong et al, 2012).…”
Section: Biomarkers As Nuclear Factor (Erythroidderived 2)-like 2mentioning
confidence: 87%
“…10 The benefits of Nrf2 signaling in human kidney disease were initially recognized in patients with cancer treated with bardoxolone, a potent Nrf2 inducer. 41 Subsequent clinical trials demonstrated that bardoxolone is effective in improving kidney function in patients with diabetes and advanced-stage CKD. 12 However, this effect was lately found to be associated with elevated albuminuria, excess serious adverse effects, and mortality caused by heart failure and cardiovascular events, which prematurely terminated the phase 3 large-scale, longterm, randomized controlled trial of bardoxolone (Bardoxolone Methyl Evaluation in Patients with Chronic Kidney Disease and Type 2 Diabetes Mellitus: the Occurrence of Renal Events) in patients with diabetic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…Of 30 assessable patients in the second study, 40% achieved disease stabilization and two objective responses were seen (Hong et al, 2008). The results of this phase 1 study have been published (Hong et al, 2012). …”
Section: Clinical Activitymentioning
confidence: 91%